A new large-bodied theropod dinosaur from the middle jurassic of Warwickshire, United Kingdom - Benson, R; Radley, J (2010)
Previously undocumented postcranial material from the Chipping Norton Limestone Formation (Middle Jurassic: Lower Bathonian) of Cross Hands Quarry, near Little Compton, Warwickshire represents a new large-bodied theropod dinosaur, distinct from the contemporaneous Megalosaurus bucklandii. Cruxicheiros newmanorum gen. et sp. nov. is diagnosed by a single autapomorphy, the presence of a proximomedially inclined ridge within the groove that marks the lateral extent of the posterior flange of the femoral caput (trochanteric fossa). C. newmanorum shows three tetanuran features: widely separated cervical zygapophyses, a swollen ridge on the lateral surface of the iliac blade and an anterior spur of the caudal neural spines. However, due to fragmentary preservation its affinities within Tetanurae remain uncertain: phylogenetic analysis places it as the most basal tetanuran, the most basal megalosauroid (= spinosauroid) or the most basal neotetanuran.